Comparative Analysis of The Economic and Environmental Performance of Virgin and Recycled Polyester in Supporting The Transition from a Linear to a Circular Economy in The Indonesian Polyester Industry - Richo Erwansyah Mauland; Jagat Prirayani (International Journal Labs, 2026)
The polyester industry in Indonesia has experienced significant growth under a linear economic model based on virgin polyethylene terephthalate (vPET), which relies heavily on fossil-based resources and contributes to high energy consumption, greenhouse gas (GHG) emissions, water use, and waste generation. The transition toward recycled polyethylene terephthalate (rPET) represents an important pathway for implementing circular economy principles and improving industrial sustainability. This study aims to compare the economic and environmental performance of vPET and rPET, evaluate future development trends, and identify strategic factors influencing the transition from a linear to a circular economy model in Indonesia’s polyester industry. A mixed-methods approach was employed, combining quantitative comparative analysis, Simple Linear Regression (SLR) for projection analysis, and PESTEL analysis to assess external factors affecting rPET development. The results indicate that vPET maintains stronger economic performance in terms of production, revenue, and operating profit; however, rPET demonstrates superior environmental performance through substantially lower energy consumption, GHG emissions, and water usage. Projection results for 2025–2030 show that rPET has greater growth potential, supported by increasing sustainability demands, regulatory pressure, technological advancement, and ESG commitments. Nevertheless, challenges related to feedstock availability, recycling infrastructure, and investment requirements remain significant barriers. This study concludes that a gradual transition through a hybrid economic approach is the most feasible strategy, enabling Indonesia’s polyester industry to balance economic competitiveness with environmental sustainability while supporting circular economy implementation and net-zero emission targets.